Rapid Detection of Contaminated Intravenous Fluids Using the Limulus In Vitro Endotoxin Assay - Jorgensen, James H. (1973)
Intravenous fluids and administration sets may become contaminated with gram-negative bacteria during use and result in a life-threatening situation to the patient. The Limulus in vitro assay for endotoxin was used in two patients whose parenteral fluids had become contaminated with Pseudomonas aeruginosa. This test allowed rapid detection of the contaminated intravenous fluids and demonstrated a concomitant endotoxemia in both patients. The same strains of pseudomon were subsequently cultured from each patient's blood, intravenous catheter tip, and parenteral fluid and administration set. A different serotype of pseudomonas was unique to each patient, indicating two separate and unrelated cases of accidental contamination of the administration sets. Endotoxin-like activity was also demonstrated from several brands of commercial human serum albumin, which may contribute low-level activity detectable by the Limulus assay.